Universal Design for Learning (UDL) as a Structure for Culturally Responsive Practice - Krista James (Northwest Journal of Teacher Education, 2018)
Alaska is rich with cultural and ethnic diversity. In fact, it is one of the three most diverse parts of the country. Culturally relevant practice both needed and required in Alaskan schools. Universal Design for Learning (UDL) is a framework that may assist educators in this endeavor. While UDL provides a framework for implementing instruction, the Alaska Cultural Standards for Educators tell us what best practice looks like for our diverse student population, especially our Alaska Native students. This article explores examples of implementation of the Alaska Cultural Standards for Educators within a UDL framework.